Practice of Participatory Local Government Planning in Nepal: Promising Provisions, Limited Implementation - Adhikari , Govinda (GS Spark: Journal of Applied Academic Discourse, 2025)
It is often emphasized in discourse that Nepal’s Date of federal system mandates participatory local planning to promote inclusive governance; however, implementation of the provisions remains limited. This study explores how participatory planning is practiced in Nepal’s local governments by analyzing legal provisions, their implementation status, and factors affecting practice. Employing qualitative methods—document analysis and literature review—the research identifies significant gaps between policy and practice. Findings reveal that although the legal framework supports inclusive planning, implementation is constrained by weak institutional capacity, limited stakeholder engagement, and entrenched power dynamics. Marginalized communities frequently lack confidence and opportunities to engage meaningfully in planning and budgeting. To address these challenges, the study recommends strengthening capacity-building initiatives for communities, institutionalizing transparent and accountable planning processes, and establishing accountability mechanisms that foster genuine participation. These measures are crucial for Nepal’s federal local governments to realize constitutional mandates for social inclusion and equitable development.